2005
DOI: 10.1111/j.1600-0765.2005.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation: a possible role in the induction and progression of chronic periodontitis

Abstract: The increased levels of lipid peroxidation may play a role in the inflammation and destruction of the periodontium in periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

42
209
4
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(262 citation statements)
references
References 57 publications
(76 reference statements)
42
209
4
7
Order By: Relevance
“…Based on these results the optimal time after tooth-brushing should be set for collection of saliva. On the other hand, better parodontal status in periodontitis patients with better oral hygiene [53] could explain decreased oxidative stress as the result of better oral hygiene. One of the drawbacks of our study is that oral hygiene and health status of the subjects were not determined.…”
Section: Effect Of Tooth-brushingmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these results the optimal time after tooth-brushing should be set for collection of saliva. On the other hand, better parodontal status in periodontitis patients with better oral hygiene [53] could explain decreased oxidative stress as the result of better oral hygiene. One of the drawbacks of our study is that oral hygiene and health status of the subjects were not determined.…”
Section: Effect Of Tooth-brushingmentioning
confidence: 99%
“…Several studies have addressed the role of oxidative stress in the pathology of oral and dental diseases, especially periodontitis [1,2,13,54] and the hypothesis that good oral hygiene may decrease oxidative stress in saliva was proposed [53]. In our study, saliva samples collected before and 10 minutes after tooth-brushing were monitored.…”
Section: Effect Of Tooth-brushingmentioning
confidence: 99%
“…36 Malodialdehyde (MDA), a thiobarbituric acid reactive substance used as a marker of lipid peroxidation to assess oxidative damage, was found increased in GCF and saliva of patients with CP. 10,37,38 Tsai et al 37 reported 200-to 400-fold higher MDA levels in GCF compared with saliva but similar salivary AO capacity. However, salivary AO capacity may have a lower prediction value for CP activity than oPMN AO capacity, considering that most oPMNs reach the oral cavity through the gingival crevices.…”
Section: Nrf2 Down-regulation In Periodontitismentioning
confidence: 99%
“…За даними нау-ковців у хворих хронічними захворюваннями паро-донту спостерігаються зміни концентрації малоно-вого диальдегіду та загального антиоксидантного статусу в сироватці, слині та ясенній рідині [3,4]. Результати численних досліджень показали, що показники перекисного окиснення ліпідів мо-жуть використовуватися при патології тканин паро-донту [5].Метою даного дослідження було вивчити ефе-ктивність запропонованої схеми профілактики і ліку-вання хронічного гінгівіту у дітей з атопічним захво-рюваннями на підставі корекції антиоксидантного дисбалансу і аналізу біомаркерів ротової рідини.Матеріали та методи дослідження. Проведене дослідження було виконано протягом 2015-2017 рр.…”
unclassified
“…За даними нау-ковців у хворих хронічними захворюваннями паро-донту спостерігаються зміни концентрації малоно-вого диальдегіду та загального антиоксидантного статусу в сироватці, слині та ясенній рідині [3,4]. Результати численних досліджень показали, що показники перекисного окиснення ліпідів мо-жуть використовуватися при патології тканин паро-донту [5].…”
unclassified